Reproductive Rights as Health Care Rights - Hill, B. Jessie (Columbia Journal of Gender and Law, 2009)
The idea that abortion rights are central to protecting women’s health will hardly come as a surprise to most reproductive rights advocates. For example, much of the recent litigation challenging states’ legal restrictions on abortion has centered around the requirement of a health exception-that is, around the question of whether legislation regulating abortion must contain an exception for cases where the regulated procedure is necessary to protect the woman’s health. Reproductive rights organizations also often espouse the language of “women’s health.” Indeed, those organizations, along with numerous other NGOs and some scholars, advocate greater recognition of the fact that reproductive health care in all of its manifestations-not just access to abortion and contraception, but also access to safe obstetric and gynecologic care, adequate prenatal nutrition and care, and sexually transmitted disease prevention-is an important part of women’s health care in general. At the same time, however, feminist legal scholars have largely shied away from discussing abortion as primarily a medical procedure, instead emphasizing the idea of abortion as an intensely personal decision and as a right that is essential to women’s equal citizenship. This framework underscores the concepts of decisional autonomy and equality underpinning the constitutional right to choose abortion. Although there are valid reasons for the emphasis taken by those reproductive rights scholars, this Article argues that it may be time to consider embracing an approach that emphasizes abortion as a form of health care.